Try NerdPal! Our new app on iOS and Android

# Solve the equation $14x-12x+39x-18x=256-60x-657x$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Videos

$x=\frac{64}{185}$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$14x-12x+39x-18x=256-60x-657x$

Specify the solving method

1

Combining like terms $14x$ and $-12x$

$2x+39x-18x=256-60x-657x$
2

Combining like terms $2x$ and $39x$

$41x-18x=256-60x-657x$

Learn how to solve one-variable linear equations problems step by step online.

$2x+39x-18x=256-60x-657x$

Learn how to solve one-variable linear equations problems step by step online. Solve the equation 14x-12x39x-18x=256-60x-657x. Combining like terms 14x and -12x. Combining like terms 2x and 39x. Combining like terms 41x and -18x. Combining like terms -60x and -657x.

$x=\frac{64}{185}$

##  Explore different ways to solve this problem

Solving a math problem using different methods is important because it enhances understanding, encourages critical thinking, allows for multiple solutions, and develops problem-solving strategies. Read more

Solve for xFind the rootsSolve by factoringSolve by completing the squareSolve by quadratic formulaFind break even points
SnapXam A2

### beta Got a different answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$14x-12x+39x-18x=256-60x-657x$